2018
DOI: 10.1186/s13023-018-0953-9
|View full text |Cite
|
Sign up to set email alerts
|

Patient and observer reported outcome measures to evaluate health-related quality of life in inherited metabolic diseases: a scoping review

Abstract: BackgroundHealth-related Quality of Life (HrQoL) is a multidimensional measure, which has gained clinical and social relevance. Implementation of a patient-centred approach to both clinical research and care settings, has increased the recognition of patient and/or observer reported outcome measures (PROMs or ObsROMs) as informative and reliable tools for HrQoL assessment. Inherited Metabolic Diseases (IMDs) are a group of heterogeneous conditions with phenotypes ranging from mild to severe and mostly lacking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 171 publications
0
33
0
Order By: Relevance
“…Health-related QoL has been gaining research momentum and clinical importance, also in inherited metabolic diseases [46]. This is a subjective measure which only the people living with (or caring for patients with) the disease can provide.…”
Section: Infections and Allergies Negatively Impact The Daily Lives Omentioning
confidence: 99%
“…Health-related QoL has been gaining research momentum and clinical importance, also in inherited metabolic diseases [46]. This is a subjective measure which only the people living with (or caring for patients with) the disease can provide.…”
Section: Infections and Allergies Negatively Impact The Daily Lives Omentioning
confidence: 99%
“…Furthermore, given the heterogeneity of the patients’ age, questionnaires were filled in by caregivers in case of minors, while adult patients filled in the questionnaire autonomously. Differences between self- and proxy-completed responses on health status surveys are well described in the literature [36, 37]. For example, some studies have reported that parents tend to assign a lower score on health-related quality of life questions regarding their children with a chronic health condition [3840].…”
Section: Discussionmentioning
confidence: 99%
“…Instruments are often not fit for purpose, and HTA evaluators are often not convinced a PROM is measuring what it is claimed to be measuring [29,31] Prior discussion with the relevant evaluating agencies can help to ensure a PROM is compatible with their standards [5,22,32] Probably feasible: This requires stakeholder willingness for planning and time commitment but has the potential to save a substantial amount of time later in the process Need for early and, if possible, iterative engagement between RDT developers and HTA evaluators Conventional methods are not always suitable for psychometric analysis in RDs because they require large samples and high-quality data [13,33,35] RD populations can be combined with populations with similar disease presentations to increase sample size [14] Feasible: Combining populations with similar disease characteristics would require guidelines and best practices, but, if done properly, provides a promising solution to overcoming the limited RD sample size Use of expert panel review to determine face validity/generalizability; hybrid conceptelicitation or cognitive interviews or linking items to international classification systems to determine content validity [11,36] Probably feasible: Qualitative data can be a good approach to ensuring validity without relying on large sample sizes but would require time and resource investment Need for recognition of the importance of, and willingness to consider, other forms of evidence in informing HRQoL impact…”
Section: Psychometric Propertiesmentioning
confidence: 99%
“…• Data are usually collected from small patient populations [12], which may result in inaccurate aggregate results. • Conditions and presentations can be heterogeneous, which make it difficult to capture meaningful and generalizable outcomes [3,[12][13][14][15]]. • Information and understanding regarding disease progression and natural history is lacking, which makes it difficult to know which PROMs to use or how to develop new PROMs [12,13,16,17].…”
Section: Introductionmentioning
confidence: 99%